Faunal analysis and injuries characterization of Polistinae (Hymenoptera, Vespidae) in niagara rosada vineyards in Bento Gonçalves, Rio Grande do Sul state, Brazil (Bioscience Journal, 2019)
The State of Rio Grande do Sul is a major producer of grapes in Brazil, highlighting the Serra Gaúcha as the main producing region. In the pursuit of good quality in grapes it is essential the control of pests, especially insects. This study highlights the incidence of wasps, which cause serious damage at harvest time. This study aimed to characterize the community of social wasps (Hymenoptera, Vespidae) through faunal analysis and to examine the relationship of these insects with injuries to the grape berries in vineyards of Bento Gonçalves, Rio Grande do Sul State. Therefore, active search were made in January and February 2014, followed by analysis of frequency, constancy, abundance, dominance and diversity. Ten species of wasps were able to use grape berries as food. The two dominant species were Polybia ignobilis and P. minarum, however, Synoeca cyanea has greater ability to break the intact berries. Other three species, Polistes cavapytiformis, P. versicolor and Brachygastra lecheguana, were also able to break the skin of grapes, but of damaged berries.